Prognostic value of c-erbB-2 expression in papillary thyroid carcinoma - Freudenberg, L. S.; Sheu, S.; Görges, R.; Mann, K.; Bokler, S.; Frilling, A.; Schmid, K. W.; Otterbach, F. (Nuklearmedizin - NuclearMedicine, 2005)
Aims: c-erbB-2 overexpression has been shown to be a potential marker of aggressive biological behaviour in a varity of tumours, whereas its role played in thyroid papillary thyroid carcinoma (PTC) remains unclear. Objective of the study is to determine whether c-erbB-2 overexpression correlates with the clinical course. Methods: We have studied 32 PTC by a two-step immunocytochemical staining procedure for paraffin-embedded specimens (DAKO Hercep- Test). Semiquantitative evaluations were performed, based on the intensity of immunostaining and the percentage of tumor cells. Results: 34% (11/32) of the PTC showed a membranous overexpression of the HER2/neu oncoprotein. Correlating the pathological and clinical data revealed that 81% (9/11) c-erbB-2 positive patients and only 33% (7/21) c-erbB-2 negative patients developed a tumor recurrence or a progression (p = 0.02 in Fisher’s exact test). 3/11 c-erbB-2 positive patients died from PTC whereas all (21/21) c-erbB-2 negative patients are still alive (p=0.03). Conclusions: Our results strongly suggest that c-erbB-2 oncoprotein overexpression is related to the clinical course of PTC.
Keywords: Papillary thyroid cancer; c-erbB-2; Her-2/neu; recurrence; oncogene